The Greenland Firn Compaction Verification and Reconnaissance (FirnCover) Dataset, 2013-2019 - Michael MacFerrin; C. Max Stevens; Baptiste Vandecrux (Arctic Data Center)
Assessing changes in the density of snow and firn is vital to convert volume changes into mass changes on glaciers and ice sheets. Firn models simulate this process but typically rely upon steady-state assumptions and a geographically- and temporally-limited set of field measurements for validation. Given rapid changes recently observed in Greenland’s surface mass balance, a contemporary dataset measuring compaction in a range of climate zones from the Greenland ice sheet’s accumulation zone is significantly needed. To fill this need, the Firn Compaction Verification and Reconnaissance (FirnCover) dataset comprises daily firn-compaction measurements from 49 strainmeters installed in boreholes at 10 accumulation sites on the Greenland ice sheet between 2013 and 2019. Two-meter air temperature and snow depth at each station were also recorded and are included with the dataset. The majority of the FirnCover stations are installed in close proximity to automated weather stations that measure a wider suite of meteorological measurements, allowing the user access to auxiliary datasets for model validation studies using FirnCover data.